Sequential embryo transfer versus double cleavage-stage embryo or double blastocyst transfer in patients with recurrent implantation failure with frozen-thawed embryo transfer cycles: a cohort study - Gao, Jiangman; Yuan, Yifeng; Li, Jia; Tian, Tian; Lian, Ying; Liu, Ping; Li, Rong; Qiao, Jie; Long, Xiaoyu; Wang, Haiyan (Frontiers in Endocrinology, 2023)
Background: Recurrent implantation failure (RIF) is more common among patients receiving in assisted reproductiveon treatment. Many efforts arehave been made to help increase the incidence of clinical pregnancy in among patients with RIF. The effect of the sequential transfer procedure, a two-step interval transfer of a cleavage-stage embryo followed by a blastocyst in one transfer cycle, on the the clinical outcomes in of RIF patients is remains still controversial.Methods: AIn total, of 1774 frozen-thawed embryo transfer (FET) cycles in RIF patients performed from January 2020 to June 2022 were included from January 2020 to June 2022. Of these cycles, 302 were sequential embryo transfer (ET) cycles, 979 were double day 3 cleavage-stage ET cycles, and 493 were double blastocyst ET cycles.The baseline characteristics and clinical outcomes of the three groups were assessed.Conclusions: Sequential embryo transfer in FET cycles could improve the clinical outcomes in of patients with RIF in FET cycles.